2022
DOI: 10.2298/gensr2202729s
|View full text |Cite
|
Sign up to set email alerts
|

Yield and taste related components variation in new superior bred strawberry genotypes and commercial cultivars during the wide harvest season

Abstract: As a result of the hybridization of ?Sevgi? and ?Ka?ka? cultivars with ?Fortuna? cultivar, which are bred within Cukurova University, superior characteristic strawberry genotypes with codes of ?33?, ?36? and ?61? were selected. In this study, these genotypes and three cultivars commonly grown in the Mediterranean region were compared in terms of yield, fruit size and taste determining parameters (sugar and organic acids) at different harvest date monthly under Mediterranean climate condition.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Also they contain a wide range of phytochemicals, including flavonoids, anthocyanins, ellagic acid, and vitamin C. Flavonoids are a type of polyphenol that are found in various fruits and vegetables, including strawberries [ 5 ]. It is demonstrated that strawberries have the antioxidative and anti-inflammatory effects, which can cope against some disease including cardiovascular and cancer [ 6 ]. Anthocyanin is a type of flavonoid that give strawberries their red color [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also they contain a wide range of phytochemicals, including flavonoids, anthocyanins, ellagic acid, and vitamin C. Flavonoids are a type of polyphenol that are found in various fruits and vegetables, including strawberries [ 5 ]. It is demonstrated that strawberries have the antioxidative and anti-inflammatory effects, which can cope against some disease including cardiovascular and cancer [ 6 ]. Anthocyanin is a type of flavonoid that give strawberries their red color [ 7 ].…”
Section: Introductionmentioning
confidence: 99%